IKHTIAR MENJADIKAN DINAR-DIRHAM SEBAGAI MATA UANG DI INDONESIA - Mursid, Ali; Muklisin, Muhammad (EQUILIBRIUM, 2013)
Paper money that we hold today is fiat money means the nominal value of money is not balanced by the intrinsic value. As a result, the day-to-day reality of the functions of money has come out of the frame that has been conceptualized in the beginning. Money should have indirect utility functions function. But it would have been eliminated with the advent sumua practice of commodity money, speculation, sagnorage and so on. This paper is made using pieces of library research methods. In this article didiskripsikan many important things about the effort to implement the dinar and dirham as currency in Indonesia. This paper aims to contribute ideas to the Indonesian people to be motivated to apply back the dinar and dirham as currency in the nation’s financial system.